Long-QT Syndrome and Therapy for Attention Deficit/Hyperactivity Disorder - Zhang, Claire (J Cardiovasc Electrophysiol, 2015)
INTRODUCTION: Stimulants are the mainstay therapy for attention deficit/hyperactivity disorder (ADHD) and are associated with adrenergic side effects. There is limited data on the clinical course of patients treated for ADHD who have long-QT syndrome (LQTS), for which β-blockade is the goal of therapy. METHODS: LQTS patients from the Rochester-based LQTS Registry (open-enrollment between 1979–2003; follow-up from 1979 to present) treated with stimulant or non-stimulant ADHD medications (n=48) were compared to a 2:1 age-, gender-, and QTc-duration matched LQTS control group not exposed to ADHD medications (n=96). Kaplan-Meier and Cox proportional hazards regression analyses were used to evaluate risk of cardiac events (syncope, aborted cardiac arrest, and sudden cardiac death) in LQTS patients treated with ADHD medications. RESULTS: During a mean follow-up of 7.9 ±5.4 years after initiation of ADHD medication at a mean age 10.7 ±7.3 years, there was a 62% cumulative probability of cardiac events in the ADHD treatment group compared to 28% in the matched LQTS control group (p<0.001). Time-dependent use of ADHD medication was associated with an increased risk for cardiac events (HR=3.07; p=0.03) in the multivariate Cox model adjusted for time-dependent β-blocker use and prior cardiac events. Subgroup gender analyses showed that time-dependent ADHD medication was associated with an increased risk in male LQTS patients (HR=6.80, p=0.04). CONCLUSIONS: LQTS patients treated with ADHD medications have increased risk for cardiac events, particularly syncope, and this risk is augmented in males. The findings highlight the importance of heightened surveillance for LQTS patients on ADHD medications.